Managing guava orchard for enhancing farmer’s income - Sharma, Akash; Wali, V K; Bhat, Anil (Indian Horticulture, 2019)
Traditional system of guava cultivation has often posed problems in attaining desired levels of productivity due to large tree canopy. Hence, a need arose to improve the existing production system, besides increasing its productivity. Currently, there is a worldwide trend in fruit trees in high-density orcharding to control tree size and maintain desired architecture for better light interception and ease in operations such as pruning, pest control and harvesting. It is well known that diversity in soil and climatic conditions in India permits cultivation of a large variety of tropical, subtropical and temperate fruits in different regions, due to which India is regarded as a horticultural paradise. In recent years, concept of fruit production is undergoing a change where emphasis is being given to higher production per unit area. High-density planting technique is a modern method of fruit cultivation involving planting of fruit trees densely, allowing small or dwarf trees with modified canopy for better light interception and distribution and ease of mechanized field operation. High-density plantation gives higher yield as well as returns/unit area due to increase in the number of trees/unit area. It is possible by regular pruning and maintaining the size and shape of the tree. High-density planting is the fastest way of increasing the productivity of the guava orchards. The choice of the planting system in the orchard depends on topography, crop, variety, plant density and production technology to be followed.